Inundações urbanas no aglomerado Rio Negro-Mafra: contribuiçôes à compreensão da dinâmica hidrológica e dos impactos na gestão urbana - John, Micheli Maclin Liebel (2021)
The frequent recurrence of floods increases the vulnerability of the urban population. This reality is repeated in the cities Rio Negro (PR) and Mafra (SC), the study area of this research, municipalities that are present in the southern region of Brazil, and that have their urban areas consolidated on the banks of the middle course of the Negro river (a tributary of the Iguaçu river). The characteristics of the Negro river basin, added to the interference of the climate that occur in the region and the consolidated urbanization that occupies much of the floodplain of this river, indicate how vulnerable the cities of Rio Negro (PR) and Mafra (SC) are to flood events. In this context, the main objective of this research is to present the understanding of the hydrological dynamics of flood events that occurred in the municipalities of Rio Negro (PR) and Mafra (SC), in the period between 1930 and 2020. This research was researched based on the series history of the Rio Negro station for the period from 1930 to 2020. The analysis showed that no period occurred 71 flood events, three of which were high and three were of extreme magnitude. In the comparison of fluviometric data made between the total series (1930 to 2020) with the reduced series (1990 to 2020) there was an increase in the frequency of events of medium and extreme magnitude. It was found that most events that occurred in the analyzed period have a return time of less than five years. Comparing the results of the return time of the reduced series with the quotas defined empirically and different in local legislation, it was found that the alert quota has a return time of two years, whereas the non aedificandi quota has a return time of ten years , and that the unrestricted quota has a payback period of fifteen years. Knowing the existence of occupations in these areas, the present study clarified that in fact such areas are frequently flooded, causing damage and losses to the population that resides in local areas.